Implementing group care in Dutch and Surinamese maternity and child care services: the vital importance of addressing outer context barriers - Nele Martens; Tessa M.I. Haverkate; Ashna D. Hindori-Mohangoo; Manodj P. Hindori; Carolien J. Aantjes; Katrien Beeckman; Astrid Van Damme; Ria Reis; Marlies Rijnders; Rianne RMJJ van der Kleij; Mathilde R. Crone (BMC, 2024)
Abstract Background By addressing physical and psychosocial needs, group care (GC) improves health-related behaviours, peer support, parent-provider interactions and may improve birth outcomes. Hence, global implementation of GC is encouraged. Context analyses prior to implementation are vital to elucidate which local factors may support or hinder implementation. Methods Contextual analyses conducted in the Netherlands and Suriname were compared to identify the factors relevant to the implementability of GC as perceived by healthcare professionals (HCPs). 32 semi-structured interviews were conducted with Dutch and Surinamese healthcare professionals. Audio recordings were transcribed verbatim and coded using the Framework approach. The Consolidated Framework for Implementation Research guided the development of the interview guide and of the coding tree. Results Outer setting: Concerns regarding funding surfaced in both countries. Due to limited health insurance coverage, additional fees would limit accessibility in Suriname. In the Netherlands, midwives dreaded lower revenue due to reimbursement policies that favour one-on-one care. Inner setting: Appropriate space for GC was absent in one Dutch and three Surinamese facilities. Role division regarding GC implementation was clearer in the Netherlands than in Suriname. Innovation: HCPs from both countries expected increased social support, health knowledge among women, and continuity of care(r). Individuals/innovation deliverers: Self-efficacy and motivation emerged as intertwined determinants to GC implementation in both countries. Individuals/innovation recipients: Competing demands can potentially lower acceptability of GC in both countries. While Dutch HCPs prioritised an open dialogue with mothers, Surinamese HCPs encouraged the inclusion of partners. Process: Campaigns to raise awareness of GC were proposed. Language barriers were a concern for Dutch but not for Surinamese HCPs. Conclusions While the most striking differences between both countries were found in the outer setting, they trickle down and affect all layers of context. Ultimately, at a later stage, the process evaluation will show if those outer setting barriers we identified prior to implementation actually hindered GC implementation. Changes to the health care systems would ensure sustained implementation in both countries, and this conclusion feeds into a more general discussion: how to proceed when contextual analyses reveal barriers that cannot be addressed with the time and resources available.